ANALISIS PERAN BIMBINGAN MANASIK KBIHU DALAM UPAYA MENINGKATKAN PEMAHAMAN PRAKTEK IBADAH HAJI PERSPEKTIF EKONOMI ISLAM - Hasan Basri; Nurbaeti Affandie; Alma Fitriya Septiani (Prodi Manajemen Haji dan Umrah Fakultas Syariah UNIK Cipasung, 2024)
This research is motivated by one of the aims of KBIHU ritual guidance is to increase KBIHU ritual guidance's understanding of the practice of the Hajj pilgrimage in a particular area. Apart from that, there is also a need for an Islamic economic review of the manasik guidance activities at the KBIHU manasik guidance. The aim of this research is to find out the role of KBIHU ritual guidance for pilgrims in KBIHU ritual guidance in understanding the practice of the Hajj pilgrimage and to find out the Islamic economics review of the role of KBIHU ritual guidance for the congregation at the KBIHU ritual guidance in Tasikmalaya City. The method used in this research uses a qualitative approach with descriptive methods and case studies. The data collection techniques used were: interviews, observation and documentation. Meanwhile, the data analysis technique uses the Miles and Huberman model, in which there are three steps in data analysis, namely: Data Reduction, Data Display, and Conclusion Drawing/Verification. The results of the research show that the KBIHU Tasikmalaya ritual guidance has a role as a place for promoting Hajj and Umrah, opening up employment opportunities and KBIHU ritual guidance and understanding local Hajj practices with income that can meet basic needs (Al-Dharuriyyah), secondary needs (Al-Hajiyyah) and tertiary needs (Al-Tahsiniyyah). Islamic Economics review of the role of KBIHU ritual guidance for pilgrims in guiding KBIHU rituals and the practice of Hajj, it is known that Hajj and Umrah business people have an honest and trustworthy attitude, carry out ijab qobul in ritual guidance with prospective pilgrims and managers of KBIHU ritual guidance who are able to direct Hajj business people and Umrah who want to borrow funds from sharia institutions to avoid usury. In this way, the KBIHU Tasikmalaya ritual guidance plays a role in guiding the KBIHU rituals and understanding the practice of the Hajj pilgrimage from an Islamic economic perspective.